Incremental Contributions of Static and Dynamic Sexual Violence Risk Assessment: Integrating Static-99R and VRS-SO Common Language Risk Levels - Olver, Mark E. (Criminal justice and behavior, 2021)
We examined the incremental contributions of static and dynamic sexual violence risk assessment in a multisite sample of 1,289 men treated for sexual offending. The study extends validation work that established new risk categories and recidivism estimates for the Violence Risk Scale–Sexual Offense version (VRS-SO), using the risk assessment common language (CL) framework. Different rates of sexual recidivism were observed at different thresholds of static risk (Static-99R) as a function of dynamic risk and treatment change, particularly for men who were actuarially above or well above average risk (Levels IVa and IVb, respectively). A framework integrating CL risk levels for Static-99R and VRS-SO dynamic scores into overall CL risk levels is presented. We discuss implications for dynamic sexual violence risk assessment regarding the language used for risk communication and the importance of dynamic risk instruments in sexual violence evaluations, particularly when credible agents of risk change may be present.